Biotic homogenization of stream macroinvertebrates in an Afrotropical Anthropocene: Land use and ecological correlates - Keke, Unique N.; Arimoro, Francis O.; Edegbene, Augustine O.; Akamagwuna, Frank C.; Assie, Fulbert A. G. J.; Odume, Oghenekaro N. (Frontiers in Environmental Science, 2022)
Land use modification is a notable cause of biodiversity loss in streams. However, the impacts of anthropogenic forest conversion on β-diversity are difficult to forecast, especially in Afrotropical stream ecosystem, mainly because: 1) empirical research is scant, and; 2) the few available studies provide conflicting findings. In our study, we used techniques of decomposing β-diversity to evaluate the influence of land use changes on macroinvertebrates β-diversity of 66 stream sites in an Afrotropical Anthropocene. We also evaluated the potential exclusive and shared contributions of ecological drivers of community composition and β-diversity. Our total β-diversity for both forested and modified streams was driven mainly by the turnover component, while the nestedness-resultant component was negligible. The dominance of turnover in both forested and modified streams in our systems stresses the urgency to protect many sites in order to conserve γ-diversity. While β-diversity diminished in our urban + agric streams in relation to our forest streams, leading to a process of biotic homogenization, β-diversity of our forest streams was similar to that of the urban streams, implying that land use does not necessarily lead to a process of biotic homogenization. The contrasting findings about relationships between land use and β-diversity in our study showed that the effects of land use on β-diversity can be variable and context-dependent. Larger parts of variation in community composition and β-diversity were accounted for by the local environmental conditions (through environmental filtering) and land use, while geographical spatial factors (through dispersal limitation) explained little part of variation in our system–highlighting the importance of species sorting (environmental filtering) over dispersal-related processes in metacommunity organization.